MODEL PENGEMBANGAN SISTEM INFORMASI AKUNTANSI TERHADAP PENGGAJIAN GURU DAN PENGURUS DI TAMAN PENDIDKAN AL-QUR’AN (TPQ) AL-MUBARAK - Mahmudah; Rika Yuliastuti; Yuliastanti, Rika (Ekomania, 2023)
The writing of this article is intended to find out the model of developing an Accounting Information System at the Al-Qur'an Education Park (TPQ) Al-Mubarak related to teacher fees at the Al-Qur'an Education Park (TPQ). The service of teaching the Koran is now very widespread, especially in the villages. TPQ Al-Mubarak has received assistance from donors and the government, so the honorarium for the Koran teacher is obtained from donors, parents, and the government. For donors who have routinely sent donations to the Al-Qur'an Education Park (TPQ) every month. The amount of donations received will be divided equally among all teachers and administrators, also the funds obtained once a year are equally divided among all teachers and administrators. The purpose of monitoring the financial statements that have been made is to prevent misinformation and communication between donors, the government, and the treasurer, because the treasurer's demands are greater than other parties regarding the finances used to pay teachers' salaries. There are two honorarium distribution systems that are implemented at TPQ A lmubarak, namely the salary paid once a month comes from donors and guardians of students while from the government once a year. once a year. The expectation is the honors are paid based on fixed salary teachers